3/8 * 5/12 = (3*5)/(8*12) = (1*5)/(8*4) = 5/32
23/4 - 5/6 = 69/12 - 10/12 = 59/12 = 4 and 11/12
5/6 times 3/4 is 5/8ths.
If the equasion is 3/4 - 5/12 then the answer is 1/3.
To determine how many times 12 can go into 53, we perform division. 53 divided by 12 equals 4 with a remainder of 5. This means that 12 can go into 53 four times, with a remainder of 5. The remainder represents what is left over after dividing as many times as possible by 12.
4 times 3 over 5 = 12/5= 4 * 3/5= 4/1 * 3/5= 12/5
3/5 x 5/12 x 4/15 = 3 x 5 x 4/5 x 12 x 15= 5 x (3 x 4)/5 x 12 x 15= 1/15
4/15 * 9/5 = 4/5 * 3/5 = 12/25
3/8 * 5/12 = (3*5)/(8*12) = (1*5)/(8*4) = 5/32
-3/5 x 4/7 is -12/35
21/36, or 7/12
(4/5)*(-3/8) = [4*(-3)]/(5*8) = -12/40 = -3/10
12 × 5/10 = 6
3/2 x 5/6 = 15/12 = 5/4 or 1 and 1/4
1/2 x 5/6 = 5/12 x 3/5 = 15/60 = 1/4
The answer is: 2 and 5/6 times 4 and 1/2 = 12 and 3/4
It is: 5/12+4/12 = 9/12 which is 3/4 in its simplest form